2014
DOI: 10.1159/000364884
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Early Catch-Up Growth on Health and Well-Being in Young Adults

Abstract: Aim: To study the effect of catch-up growth in the 1st year on cognition, health-related quality of life (HRQoL), problem behavior and growth in young adults. Methods: We included individuals without severe complications and born small for gestational age (SGA; n = 228 for weight, n = 203 for length) or with a low head circumference (HC, n = 178) or a low weight adjusted for length (n = 64) in the Collaborative Project on Preterm and SGA Infants. Neonatal growth was standardized (standard deviation scores for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…One way to look at weight or length/height patterns is to subtract weight or length/height at an earlier age from a later age. In this issue, Van Dommelen et al explored the impact of gain in weight and length in the first year on cognition, health-related quality of life and problem behavior in young adults born small for gestational age [18] In this Dutch study, the exposure variable was weight or length SDS at 1 year of age adjusted for weight or length SDS at birth. They showed that a higher weight growth in the first year was associated with better cognition and fewer disabilities, but not with problem behavior.…”
Section: Predictionmentioning
confidence: 99%
See 1 more Smart Citation
“…One way to look at weight or length/height patterns is to subtract weight or length/height at an earlier age from a later age. In this issue, Van Dommelen et al explored the impact of gain in weight and length in the first year on cognition, health-related quality of life and problem behavior in young adults born small for gestational age [18] In this Dutch study, the exposure variable was weight or length SDS at 1 year of age adjusted for weight or length SDS at birth. They showed that a higher weight growth in the first year was associated with better cognition and fewer disabilities, but not with problem behavior.…”
Section: Predictionmentioning
confidence: 99%
“…They showed that a higher weight growth in the first year was associated with better cognition and fewer disabilities, but not with problem behavior. [18] Another way to look at weight-for-length patterns is to divide it into different age intervals of biological interest. An example of this approach is the work carried out by Belfort et al who looked in a cohort from the 1980s, at weight gain, linear growth and weight for length gain and divided this into term to 4 months and 4–12 months.…”
Section: Predictionmentioning
confidence: 99%
“…Postnatal catch-up growth is both beneficial and detrimental. While it provides early survival and neurodevelopmental advantages [9,10], there is evidence that the development of cardiometabolic disease in adulthood is related to early key growth periods. These include the period of in utero fetal growth resulting in low birth weight, and early infancy where catch-up growth occurs [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…In general, repeating previous analyses with newly imputed data may result in different parameter estimates or conclusions. We demonstrate this with an adapted example from Van Dommelen et al (2014). The researchers used the POPS data to predict the effect of early catch-up growth (developing toward the median of the growth charts in the first year of life) on health and well-being in young adulthood from the POPS data.…”
Section: Problem Illustrationmentioning
confidence: 98%